2022
DOI: 10.1038/s41598-022-11483-3
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural network for automatic maxillary sinus segmentation on cone-beam computed tomographic images

Abstract: An accurate three-dimensional (3D) segmentation of the maxillary sinus is crucial for multiple diagnostic and treatment applications. Yet, it is challenging and time-consuming when manually performed on a cone-beam computed tomography (CBCT) dataset. Recently, convolutional neural networks (CNNs) have proven to provide excellent performance in the field of 3D image analysis. Hence, this study developed and validated a novel automated CNN-based methodology for the segmentation of maxillary sinus using CBCT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Segmentations in Table 3 illustrate the types of required refinements per segmented structure. According to previous validation studies’ classification [ 12 , 13 ], minor refinements have no or slight clinical relevance, and the present qualitative analysis assumes that this clinical impact depends on the number of minor refinements needed. In daily practice, the clinical relevance of such refinements might differ depending on the task at hand, such as visualization, diagnosis, treatment planning, and patient education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Segmentations in Table 3 illustrate the types of required refinements per segmented structure. According to previous validation studies’ classification [ 12 , 13 ], minor refinements have no or slight clinical relevance, and the present qualitative analysis assumes that this clinical impact depends on the number of minor refinements needed. In daily practice, the clinical relevance of such refinements might differ depending on the task at hand, such as visualization, diagnosis, treatment planning, and patient education.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative assessment revealed that the sum of mean time required for automatic MVP segmentation (1.7 min) was slightly higher compared to the sum of the previously documented timing for each structure segmentation which totaled 1.3 min (maxillofacial complex: 39.1, maxillary sinus: 24.4, all teeth: 13.7 s) [ 8 , 12 , 13 ]. This minimal difference could be attributed to some technical variabilities, such as nonuser active processes, which impact the segmentation time even if the same AI tool is run several times, making it a challenge to keep the time constant [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, 3D convolution followed by 3D max-pooling was adopted in its encoder path, with 3D up-sampling together with the spatial information during encoding in decoder path. This architecture has been tested in various scenarios of medical imaging, with robust performance [ 16 , 21 ]. Additionally, it is noteworthy that novel variants of U-Net have been proposed, which are believed to be methodologically superior, including UNeXt, nnU-Net, cascaded U-Net, U-NetCC, double U-Net, and recurrent residual U-Net [ 1 , 11 , 13 – 15 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are many research works on artificial intelligence including machine learning that can help clinicians detect abnormal findings in the maxillary sinus from CBCT images [ 87 ]. To begin with, convolutional neural network (CNN) could be used to automatically segment the maxillary sinus into the bone, air and lesion [ 88 , 89 ], such as MRC [ 90 ] or even complete opacification [ 91 ]. CNN could also be used to classify if a maxillary sinus was healthy or with sinusitis [ 92 ], and to detect the location of the maxillary sinus floor and automatically measure the associated alveolar ridge height for implant planning [ 93 ].…”
Section: Artificial Intelligence In Sinus Diagnosismentioning
confidence: 99%